Two new species of the genus Indigofera (Papilionoideae, Leguminosae) from central Mexico - Rzedowski, Jerzy; Grether, Rosaura (Phytotaxa, 2018)
Two new species of Indigofera from central Mexico are described and illustrated. Indigofera sousae, from northwestern Michoacán, is related to I. constricta known in the Mexican states of Sinaloa to Guerrero. Indigofera uniseminalis, from northeastern Guanajuato, is similar to I. sphaerocarpa, reported from southwestern United States and northwestern Mexico, and to I. jaliscensis, of the Sierra Madre Occidental and the Transmexican Volcanic Belt.